Non-genetic Heterogeneity of Macrophages in Diseases—A Medical Perspective - Gessain, Grégoire; Blériot, Camille; Ginhoux, Florent (Frontiers in Cell and Developmental Biology, 2020)
Macrophages are sessile immune cells with a high functional plasticity. Initially considered as a uniform population of phagocytic scavengers, it is now widely accepted that these cells also assume developmental and metabolic functions specific of their tissue of residence. Hence, the paradigm is shifting while our comprehension of macrophage heterogeneity improves. Accordingly, exploiting this intrinsic versatility appears more and more promising for the establishment of innovative therapeutic strategies. Nevertheless, identifying relevant therapeutic targets remains a considerable challenge. Herein, we discuss various features of macrophage heterogeneity in five main categories of human diseases: infectious, inflammatory, metabolic, age-related and neoplastic disorders. We summarize the current understanding of how macrophage heterogeneity may impact the pathogenesis of these diseases and propose a comprehensive overview with the aim to help in establishing future macrophage-targeted therapies.